Design of Islamic Education Policy Based on Human Resource Competence - Inganatul Khasanah (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Human resource (HR) competency is an important element in supporting organizational success. Competency refers to the ability, knowledge, skills, attitudes, and characteristics of individuals needed to carry out tasks optimally. Competency-based HR management emphasizes the importance of mapping competencies that are in accordance with job needs, as well as individual development through training and skills improvement programs. The purpose of HR competency management is to ensure that each position can function according to job demands and increase the effectiveness and efficiency of the organization. In addition, HR competency management can provide benefits to employees, such as increased skills, career development opportunities, and increased job satisfaction. For organizations, the benefits include recruitment effectiveness, accurate competency mapping, and better change management. Therefore, effective HR competency management will support the achievement of organizational goals and increase the company's competitiveness.